(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In this article, the linguistic, cultural features of paremological units in English and Uzbek are analyzed. Paremiological units are a short form of folk oral creativity, such as proverb, aphorism, phrase. During the study, paremological units in two languages are compared in terms of shape, content and application. They also reflect the national mentality, values and worldviews through them. The article is also focused on the problems and solutions that occur during the identification of inter-speaking similarities and differences.